The Combined Effect of Subjective Body Image and Body Mass Index (Distorted Body Weight Perception) on Suicidal Ideation - Jaeyong Shin; Young Choi; Kyu-Tae Han; Sung-Youn Cheon; Jae-Hyun Kim; Sang Gyu Lee; Eun-Cheol Park (Korean Society for Preventive Medicine, 2015)
Objectives: Mental health disorders and suicide are an important and growing public health concern in Korea. Evidence has shown that both globally and in Korea, obesity is associated with an increased risk of developing some psychiatric disorders. Therefore, we examined the association between distorted body weight perception (BWP) and suicidal ideation. Methods: Data were obtained from the 2007-2012 Korea National Health and Nutritional Evaluation Survey (KNHANES), an annual cross-sectional nationwide survey that included 14 276 men and 19 428 women. Multiple logistic regression analyses were conducted to investigate the associations between nine BWP categories, which combined body image (BI) and body mass index (BMI) categories, and suicidal ideation. Moreover, the fitness of our models was verified using the Akaike information criterion. Results: Consistent with previous studies, suicidal ideation was associated with marital status, household income, education level, and perceived health status in both genders. Only women were significantly more likely to have distorted BWP; there was no relationship among men. In category B1 (low BMI and normal BI), women (odds ratio [OR], 2.25; 95% confidence interval [CI], 1.48 to 3.42) were more likely to express suicidal ideation than women in category B2 (normal BMI and normal BI) were. Women in overweight BWP category C2 (normal BMI and fat BI) also had an increased OR for suicidal ideation (OR, 2.25; 95% CI, 1.48 to 3.42). Those in normal BWP categories were not likely to have suicidal ideation. Among women in the underweight BWP categories, only the OR for those in category A2 (normal BMI and thin BI) was significant (OR, 1.34; 95% CI, 1.13 to 1.59). Conclusions: Distorted BWP should be considered an important factor in the prevention of suicide and for the improvement of mental health among Korean adults, especially Korean women with distorted BWPs.